Is nutritional support needed in late preterm infants? - Giannì, Maria Lorella (BMC Pediatr, 2015)
BACKGROUND: Late preterm birth accounts for 70 % of all preterm births. While the impact of feeding problems in very preterm infants has been widely investigated, data on late preterm infants’ feeding issues are scarce. The aim of the present study was to investigate the need of nutritional support during hospital stay in a cohort of late preterm infants and to identify the factors that most contribute to its occurrence. METHODS: We analyzed the medical records of late preterm infants, born 2011–2013, admitted to a single institution. Neonatal data, the need for nutritional support, defined as the need for parenteral nutrition or intravenous fluids or tube feeding, and the feeding status at discharge were retrieved. The occurrence of respiratory distress syndrome, congenital malformations/chromosomal diseases, cardiac diseases, sepsis, hypoglycemia, poor feeding and the need for surgical intervention were also collected. RESULTS: A total of 1768 late preterm infants were included. Among the 592 infants requiring a nutritional support, 228 developed a respiratory distress syndrome, two developed a sepsis, one presented with a cardiac disease, 24 underwent a surgical intervention, eight had a chromosomal disease/congenital malformation, 80 had hypoglycemia. In addition, 100 infants required nutritional support due to poor feeding and 149 were born small for gestational age. Birth weight ≤2000 g (adjusted OR = 12.2, 95 % CI 7.5-19.9, p < 0.0001), gestational age of 34 weeks (adjusted OR = 4.08, 95 % CI 2.8-5.9, p < 0.0001), being small for gestational age (adjusted OR = 2.17, 95 % CI 2.8-5.9, p=0.001), having a respiratory distress syndrome (adjusted OR = 79.6, 95 % CI 47.2-134.3, p < 0.0001) and the need of surgical intervention (adjusted OR = 49.4, 95 % CI 13.9-174.5, p < 0.0001) were associated with a higher risk of need of nutritional support during hospital stay. CONCLUSIONS: Late preterm infants are at relatively high risk of requiring nutritional support during hospital stay, especially if they have a birth weight ≤2000 g, a gestational age of 34 weeks, are born small for gestational age, develop a respiratory distress syndrome and require a surgical intervention. The present findings add to the knowledge of late preterm infants’ feeding issues and may contribute to tailoring nutritional approaches for these infants.